Birth intervals and infant mortality in La Cabrera (Spain) - Blanco-Villegas, María José (Array, 2009)
Abstract: Family reconstitution has provided knowledge about the reproductive performance of mates from La Cabrera (northwest Spain). The analysis of 2293 reconstituted families (7872 births corresponding to parities 2 to 10) was restricted to the period 1880 to 1929. The proportion of infant deaths (younger than 1 year) was calculated regarding the preceding birth interval and the death or survival of the previous sibling. Considering as dependent variables the neo and the postneonatal mortality, a logistic regression was obtained. From the present analysis it is concluded that in La Cabrera 45% of couples have the most effective reproduction with birth intervals of 24 to 36 months. Risk factors regarding neonatals were found to be intervals shorter than 17 months, the death of the preceding sibling and male sexuality. Neither maternal age nor the accumulated number of previous sibling deaths were significant risk factors